Šiaurės žemaičių priebalsių diferencinių požymių sistema - Kliukienė, Regina (Kalbotyra, 1998)
The acoustic analysis of the North Žemaitian consonants enables to identify consonantal phonemes of the dialect using the following differential features: 1. sharp-plain; 2. voiced-unvoiced; 3. nasal-oral; 4. compact-diffuse; 5. acute-grave; 6. strident-melow; 7. continuant-discontinuous; 8. sonorant-obstruent.